Between Real Estate Funding and Financialization: the State-Market Nexus in Housing Policy Governance - Abreu, Marlon Altavini de (2024)
The paper scrutinizes the course of the housing financialization process in Brazil, with a focus on the pivotal role played by Caixa Econômica Federal (cef) as the primary financier for housing production and consumption. The paper aims to elucidate the intricate interplays between the State and the Market by meticulously systematizing data on securitized bond issuances and critically examining how the former deploys financial mechanisms and instruments to conduct its objectives in housing policy.